(untitled) (Laisvalaikio tyrimai, 2018)
Research background. Alcohol consumption and behaviour related to it is a widely discussed topic. World Health Organization (WHO) reports 2.5 million annual deaths caused by the harmful use of alcohol. The use of alcohol puts risk on just on the individual level, but compromises the well-being of the society. Although a variety of researches focuses exclusively on teenagers, student and adolescence alcohol use issues (Deshpande, Rundle-Thiele, 2011; Sancho et al., 2011; Varela, Pritchard, 2011; Marcoux, Shope, 1997; Burns et al., 1993) the investigation in to relation between health consciousness, attitudes toward alcohol advertising and alcohol drinkers and their effect on adult alcohol purchase intention is scarce. The object of the research is to examining adult alcohol purchase intention phenomenon influenced by individual’s health consciousness, attitude toward advertising, and attitude toward drinkers Methods. The data for this research was collected on December, 2013. A total of 388 filled questionnaires were collected to perform the research. Structural equation modelling (Lisrel 9.1) tools were used to test the proposed hypotheses. Results. The findings reveal that health consciousness and attitude toward alcohol advertising have a significant negative effect on alcohol purchase intention among adult population, while attitude toward alcohol drinkers indicates significant positive effect. Conclusions. Adult alcohol purchase intention is a complex phenomenon influenced by both of social and personal determinants. This research paper revealed that consumer’s inner characteristics those of health consciousness, attitudes toward alcohol advertising and alcohol drinkers have an effect on adult’s alcohol purchase intention. Conclusively, these finding could be ultimately used while seeking the reduction of alcohol amounts consumed. Keywords: alcohol, health-consciousness, attitudes toward alcohol advertising, attitudes toward drinkers.